'At the desire of several persons of quality and lovers of Musick': pervasive and persuasive advertising for public commercial concerts in London 1672–1749. Issue 13 (2nd September 2017) - Harbor, Catherine
ABSTRACT: The late seventeenth and eighteenth centuries saw the development in London of the public commercial concert which made early and increasing use of the newspaper as a method of advertising. This was both an innovation for promotion of commercial entertainments and a huge rise in pervasiveness over existing methods such as flyers and bills. A detailed analysis of the advertisement texts shows how they used various advertising techniques to convey a persuasive message about the concert and employed concepts such as novelty, quality, and appeals to class, status and self-identity. Moving beyond the argument that early advertisements could be persuasive, this paper identifies and interprets the techniques of persuasion musicians used and discusses how they foreground those found in more recent and current advertising practice.